Who's afraid of the dark? - Bonsall, Crosby, 1921-1995. ([New York] : HarperCollins Publishers, 2002)
A young boy tells his friend that his dog, Stella, is afraid of the dark, but Stella knows the truth about who really is fearful at night.
"Level 1, preS-grade 1"--Cover.
Wilson's Children, October 2010
Elem. School Library Collection, March 1998
Horn Book, September 1998
Bulletin (Center for Children's books), May 1998
Kirkus Review, September 1998
Keywords: Fear of the dark -- Fiction; Dogs -- Fiction; Fear of the dark -- Fiction; Dogs -- Fiction; Readers (Elementary)